4CPS-015 Evaluation of anticoagulants misuse in patients admitted for ischaemic stroke in a neurology unit. (March 2019) - Bagur, N; Janes, A; Richard, H; Roux, C; Kinowski, JM
Abstract : Background: We presume that some ischaemic strokes (IS) can be caused by a misuse (prescription errors or lack of compliance) of oral anticoagulant medications (vitamin K antagonists (VKA) or direct oral anticoagulant (DOA)). Purpose: To define the proportion of iatrogenic IS for patients admitted in a neurology unit. Material and methods: A prospective, single-centre, descriptive study was conducted during 5 months. Age, sex, CHADS VASC, HAS BLED scores and IS etiology were evaluated for 75 patients. Their anticoagulant treatments before hospitalisation were analysed. The four-item Morisky medication adherence scale (MMAS-4) was used to assess compliance. Results: The mean age was 72 years. Fifty-six per cent of patients were male. CHADS VASC and HAS BLED scores were respectively 3, 4/9 and 2, 9/9. Twenty-nine IS were caused by atrial fibrillation, 13 by atheromatous stenosis, seven by deep vein thrombosis, one by an intra-cardiac thrombus, one by antiphospholipid syndrome, one by cerebral amyloid angiopathy and none by pulmonary embolism. Twenty-three causes remain unknown. Mean compliance score was 2, 5/4 for 61% of patients (29 patients were not evaluated). Twelve patients (16%) were pretreated with anticoagulants before their hospitalisation: six patients by DOA (two apixaban, four rivaroxaban) and six patients by VKA (five fluindione, one warfarin). All DOA prescriptions were in accordance with the guidelines, but compliance scores were low: 2/4 for two patients out of six, 1/4 for one patient and 0/4 for one patient (data were missing for the remaining two). The compliance score for VKA was evaluated for only one patient: the score was 2/4. The International Normalised Ratio (INR) before hospitalisation was within the therapeutic range for the patient treated with warfarin and for one patient out of five under fluindione. Data were consistent with the literature. Conclusion: Some patients admitted for IS were pre-treated for a thromboembolic pathology. Compliance scores were low for DOA and a majority of INR before hospitalisation was not within the therapeutic range. The risk of developing an IS was thus increased for these patients. Implementing educational programmes, involving community pharmacists and stressing the importance of INR monitoring seem to be the potential axis of improvement to promote patients' compliance. References and/or acknowledgements: https://www.ncbi.nlm.nih.gov/pubmed/17186395 No conflict of interest.